Migrant women on the labour market: On the role of home- and host-country participation - Suzanne Kok; Nicole Bosch; Anja Deelen; Rob Euwals (Institute for the Study of Labor (IZA), 2011)
The behaviour of migrant women on the labour market is influenced by a variety of factors, among which the culture of the home and host country. Part of the literature investigates the role of home-country culture. This study extends the literature by including a measure for the influence of host-country culture as an additional determinant of the participation of migrant women. The empirical model explains participation from demographics and educational attainment, and uses home- and host-country female participation as proxies for culture. Evidence on the basis of the Dutch Labour Force Survey 1996-2007 suggests that both differences in home-country female participation and the trend in native female participation, as a measure for host-country culture, affect the participation of migrant women. The results suggest that host-country participation is at least as important as home-country participation.
urn:nbn:de:101:1-201107042664
Keywords: J16; J22; J61; 330; female labour force participation; immigration; cultural transmission